Aspects of urban transportation drivers' perceptions of driving security - Fernando Miguel; Martins Guterres; Arajeo Freitas (Institute of Accounting Research and Novation (IARN), 2022)
The purpose of this cross-sectional study done between December 2009 and February 2010 is to identify which factors are connected with the perception of public transit drivers regarding road safety. According to the results of the study, the elements linked with angkutan kota drivers' opinions of road safety are their knowledge of road safety, their motivation towards road safety, and their experience with accidents and tickets while driving. While the knowledge variable is the most influential factor influencing public transit drivers' perceptions of road safety, other variables also play a role. This indicates that angkutan kota drivers with greater knowledge are 3,790 times more likely to have a positive perception than those with less information. Therefore, it is suggested that angkutan kota owners and related parties (Police and Road Transport Traffic Office), if they want to improve the perception of angkutan kota drivers to drive more safely, build the knowledge and motivation of angkutan kota drivers by holding trainings and mini-workshops on the dangers of accidents while driving.